2014
DOI: 10.1212/wnl.0000000000000181
|View full text |Cite
|
Sign up to set email alerts
|

Brain imaging of cognitively normal individuals with 2 parents affected by late-onset AD

Abstract: Objectives: This brain imaging study examines whether cognitively normal (NL) individuals with 2 parents affected by late-onset Alzheimer disease (LOAD) show evidence of more extensive Alzheimer disease pathology compared with those who have a single parent affected by LOAD.Methods: Fifty-two NL individuals received MRI, 11 C-Pittsburgh compound B (PiB)-PET, and 18 F-fluoro-2-deoxyglucose (FDG)-PET. These included 4 demographically balanced groups (n 5 13/group, aged 32-72 years, 60% female, 30% APOE e4 carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 39 publications
(83 reference statements)
5
38
0
Order By: Relevance
“…Similar changes have been reported in cognitively normal individuals at high risk for AD due to expression of the ApoE4 alelle (Reiman et al, 1996; Small et al, 2000). Further, hypometabolism has been reported in cognitively normal individuals with a parent with AD (Mosconi et al, 2009; Mosconi et al, 2014; Mosconi et al, 2008a; Mosconi et al, 2013). Changes in cerebral metabolism also have been detected in MCI in many studies (Arnaiz et al, 2001; Chetelat and Baron, 2003; Chetelat et al, 2003; Del Sole et al, 2008; Garibotto et al, 2008; Li et al, 2008a; Li et al, 2008b; Mevel et al, 2007; Mosconi et al, 2006; Mosconi et al, 2008b; Perneczky et al, 2007).…”
Section: Cerebral Glucose Metabolism Imaging Using Fdg Petmentioning
confidence: 94%
“…Similar changes have been reported in cognitively normal individuals at high risk for AD due to expression of the ApoE4 alelle (Reiman et al, 1996; Small et al, 2000). Further, hypometabolism has been reported in cognitively normal individuals with a parent with AD (Mosconi et al, 2009; Mosconi et al, 2014; Mosconi et al, 2008a; Mosconi et al, 2013). Changes in cerebral metabolism also have been detected in MCI in many studies (Arnaiz et al, 2001; Chetelat and Baron, 2003; Chetelat et al, 2003; Del Sole et al, 2008; Garibotto et al, 2008; Li et al, 2008a; Li et al, 2008b; Mevel et al, 2007; Mosconi et al, 2006; Mosconi et al, 2008b; Perneczky et al, 2007).…”
Section: Cerebral Glucose Metabolism Imaging Using Fdg Petmentioning
confidence: 94%
“…114 Glucose metabolism in the brain is established as being critical to neurological function and that evidence of hypometabolism is apparent several decades before diagnosis of neurodegenerative diseases such as Alzheimer disease. [115][116][117] Depression Increased risk of depression in perimenopausal women is supported by evidence from several longitudinal studies that have documented odds ratios ranging from 1.8 to 2.9 of increased risk compared with women in premeno pause. 33,35,36 During perimenopause, both hot flushes and depression can occur early in the transition in women with no previous history of these symptoms although depression was more likely to precede hot flushes.…”
Section: Hot Flushesmentioning
confidence: 98%
“…In the hypothesis of the amyloid cascade and in a recently formulated hypothetical biomarker model, they were put downstream to amyloid and tau deposition . However, studies in subjects at risk of AD, for example, young ApoE4 carriers (Reiman et al, 2004;Scarmeas et al, 2003;Wierenga et al, 2013) or subjects with a family history of AD (Mosconi et al, 2014), have revealed alterations in glucose metabolism and CBF. Thus, a very early and causative effect might be possible.…”
Section: Risk Factors Of Ad and Cbfmentioning
confidence: 99%